2008
DOI: 10.1007/s00104-008-1532-8
|View full text |Cite
|
Sign up to set email alerts
|

Weniger Refluxrezidive nach Nissen-Fundoplikation

Abstract: Overall results are satisfactory after 10 years of experience with fundoplication. Total fundoplication appears to control reflux better than partial fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
1
0
0
2
Order By: Relevance
“…Similar poor results were reported by Watson's group [15,41]. A 10-year retrospective study from Fein [43] involving 120 patients also showed that regurgitation persisted in only 15 % LPF patient compared to 44 % LAF patient. It is therefore evident from the various RCTs that LPF (Nissen and Toupet) produces far superior reflux control compared to LAF.…”
Section: Discussionsupporting
confidence: 73%
“…Similar poor results were reported by Watson's group [15,41]. A 10-year retrospective study from Fein [43] involving 120 patients also showed that regurgitation persisted in only 15 % LPF patient compared to 44 % LAF patient. It is therefore evident from the various RCTs that LPF (Nissen and Toupet) produces far superior reflux control compared to LAF.…”
Section: Discussionsupporting
confidence: 73%
“…Die Standardisierung des laparoskopischen Zugangs führte zu weiter steigenden Operationszahlen. Interessanterweise belasteten diese Entwicklungen die Ergebnisse der Antirefluxchirurgie in den folgenden Jahren, wahrscheinlich sowohl durch unangemessene Indikationsstellungen als auch durch die Verbreitung der Operationen in Kliniken, die weniger Erfahrung in Diagnostik und operativer Therapie der GERD aufwiesen [41,42].…”
Section: Rationale Für Neue Operative Verfahren Der Gerdunclassified
“…Nach einigen Jahren der Angelchik-Euphorie häuften sich die Komplikationen, die sehr eindeutig in Korrelation mit der Nutzungsdauer des Implantats kontinuierlich anstiegen, sodass die Methode in den 1990er-Jahren verlassen wurde [22]. Mit der in dieser Zeit zunehmend kultivierten Modifikation der klassischen Fundoplikationsmanschette in Form einer Verkürzung, Lockerung und Weitung ließen sich in erfahrener Hand in hohem Maße zufriedenstellende Ergebnisse realisieren [23,24]. Die Standardisierung des laparoskopischen Zugangs führte zu weiter steigendem Interesse an der operativen Therapiealternative für chronisch Refluxkranke, sowohl seitens der Patienten als auch der Chirurgen.…”
Section: Innovative Techniques In Reflux Surgeryunclassified